Harold Tarrant, Danielle A. Layne, Dirk Baltzly and François Renaud (eds.) Brill’s Companion to the Reception of Plato in Antiquity, Brill, Leiden-Boston 2018, pp. 657, ISBN 978-90-042-7069-5 - Boeri, Marcelo (ΠΗΓΗ/FONS, 2020)
--